Structural Damages Identification and Maintenance Design of Sports Facilities for Improving Performance and Infrastructure Resilience - Utari, Virda; Astuti, Pinta (Universitas Muhammadiyah Yogyakarta, 2024)
Building maintenance is vital to ensure facility reliability, security, and investment value, as neglect can lead to structural decay and safety hazards. This study aims to assess the deterioration level of sports facilities at PT SIER and devise an efficient maintenance plan. The process involves identifying structural damages, evaluating deterioration following guidelines, and planning maintenance actions. Subsequent steps include budgeting, creating Work Plans and Specifications, estimating Domestic Component Levels, and scheduling using the S-Curve. Analysis reveals varying degrees of architectural degradation, ranging from 1 to 3, signifying serious damage. The estimated total cost for upkeep and development is Rp 255,718,000, with a projected minimum Duty and Customs Levies value of 30.43%. Maintenance duration is estimated at 45 days, managed using the S-Curve method.